Postural Control and Sensory Processing in Preschool Children with Autistic Spectrum Disorder: A Cross-Sectional Study - Marta Ferreiro-Pérez; Vanesa Abuín-Porras; Patricia Martín-Casas; Rosa M. Ortiz-Gutiérrez (MDPI AG, 2024)
The role of sensory processing in maintaining postural control (PC) among preschool-aged children with autism spectrum disorder (ASD) remains underexplored despite its potential implications for their developmental trajectory. This study aimed to assess the utilization of sensory information for PC maintenance while standing in preschool-aged children with ASD and to examine its correlation with PC during functional tasks using a standardized tool. The cross-sectional study recruited 27 children, aged between 3 and 6 years, diagnosed with ASD. Participation indexes for somatosensory, vestibular, visual, and visual preference were computed during a modified Clinical Test of Sensory Integration and Balance (m-CTSIB), based on sagittal plane body sway analyzed via video with Kinovea® software (version 0.9.4). Additionally, scores from the Pediatric Balance Scale (PBS) were analyzed. Statistical analysis of data derived from lateral malleolus and mastoid process sway using the Friedman test revealed significant differences in the utilization of various sensory systems involved in PC during the m-CTSIB (p < 0.001). There was a pronounced reliance on somatosensory information, coupled with increased instability in the absence or with the variability of visual information. The mean PBS score was 50.44 ± 2.74, exhibiting a significant negative correlation with the vestibular index (p < 0.05). Preschool-aged children with ASD demonstrated challenges in maintaining PC while standing under different sensory conditions, indicating a heightened dependence on somatosensory cues, particularly in the absence or with the variability of visual stimuli. While these challenges were not reflected in PBS scores, they were negatively correlated with the vestibular index.